STUDI TIMBULAN LIMBAH BAHAN BERBAHAYA DAN BERACUN SISA DAN KEMASAN OBAT PADA RUMAH TANGGA KOTA DENPASAR - Nisa, Anita Hayatun; Sujaya, I Nengah (ARCHIVE OF COMMUNITY HEALTH, 2025)
ABSTRACT The city of Denpasar, which acts as the capital of the Province of Bali, is of course the center of government, the center of the economy and the center of education. According to the Central Statistics Agency for Denpasar City, the population of Denpasar City in 2020 is 962,900 people and the number of households is 292,600 households. As the population increases, the amount of waste generated and its problems also increase. The purpose of this study was to determine the generation of hazardous and toxic waste materials and drug packaging as well as the management behavior carried out at the household level. This research is a cross-sectional study with a quantitative descriptive research design conducted in the city of Denpasar. The variables measured in this study consisted of age, education level, knowledge, facilities, policies based on Lawrence Green's theory. The results showed that the respondent's behavior was still negative with a percentage of 71%. Based on the results of the analysis carried out, the knowledge variable has a relationship with the behavior variable with a p-value = 0.027. Meanwhile, the variables of age, level of education, facilities and policies have no relationship with the behavior of respondents in managing the remaining B3 waste and drug packaging produced. The generation of residual B3 waste and drug packaging produced by households reached 0.0016 kg/household/day. Keywords: Hazardous waste generation, behavior, knowledge, household